STRATEGIES FOR INCREASING THE PERFORMANCE OF EMPLOYEES IN. BANK RAKYAT INDONESIA (PERSERO) TBK UNIT BULUMARIO PASANGKAYU CITY - Muhammad Arfah (Universitas Muhammadiyah Makassar, 2021)
The background of this purchasing problem is taken from the presence od employees who are not in accordance with existing abilities or slills so that they do not work and are delayed in a job. The type of research used is descriptive qualitative in which the authors describe the results describe the results of observations and direct interviews with the head of the bullumary unit and employees at PT. Bank Rakyat Indonesia (Persero) Tbk Bulumario Unit Pasangkayu City. Wring the final project is the result of writing done in june to july 2020. Research as outlined in this thesis aims to determine the strategy for developing employee performance in PT. Bank Rakyat Indonesia (Persero) Tbk Bulumario Unit Pasangkayu City. The results showed that the strategy for developing employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Bulumario Unit In Pasangkayu City consists of 1. Improving discipline 2.Conducting training 3.Career path 4.Providing benefits to amployee 5.Maintaining good relations between employees.